Removal of ferrum (II) from industrial wastewater using water hyacinth (Eichhornia Crassipes) - Nor Aznirah, Abdullah (2010)

(untitled)
Heavy metals have been excessively released into the environment due to rapid industrialization and have created a major global concern. Cadmium, zinc, copper, nickel, lead, mercury and chromium are often detected in industrial wastewaters, which originate from metal plating, mining activities, smelting, battery manufacture, tanneries, petroleum refining, paint manufacture, pesticides, pigment manufacture, printing and photographic industries. The main purpose of this research is to study the capability of water hyacinth in removing Ferum (II) from industrial wastewater. The scope of this study is divided to two which is the effect of contact time and the effect of amount water hyacinth on Ferrum (II) removal. For the methodology, firstly, the biosorbent which is water hyacinth was collected from ponds, lake and swamp nearby UMP. Then, the biosorbents were washed from any dirt particles and impurities. The sample of wastewater was collected from Hunstman Tioxide Industries. The capacity of Ferrum absorbed by water hyacinth was measured in this experiment by determining the concentration of Ferrum before and after the addition of biosorbent by using UV-Vis spectrophotometer. From the obtained result, the percentage removal of Ferrum (II) from the industrial wastewater is increases with increasing the contact time and the amount of aquatic plants. Water hyacinth exhibits high potential for wastewater treatment because of its ubiquity, rapid growth rate, ease of harvest and extended growing and harvesting periods. Therefore the water hyacinth could be harvested in water systems to remove heavy metals effectively, and hence indicates the potential of these plants for pollution monitoring of these metals.